Lifetime Psychosocial Stress Exposure Associated with Hypertensive Disorders of Pregnancy - Caplan, Madeleine; Keenan-Devlin, Lauren S.; Freedman, Alexa; Grobman, William; Wadhwa, Pathik D.; Buss, Claudia; Miller, Gregory E.; Borders, Ann E.B. (American Journal of Perinatology, 2020)
Objective Hypertensive disorders of pregnancy (HDP) complicate 5 to 10% of all pregnancies and are a major cause of pregnancy-related morbidity. Exposure to psychosocial stress has been associated with systemic inflammation and adverse birth outcomes in pregnant women. Thus, it is probable that psychosocial stress and inflammation play a role in the development of HDP. The primary objective of this analysis was to determine if a woman's lifetime psychosocial stress exposure was associated with an increased risk of HDP. Additionally, we examined whether serum inflammation was an underlying biological mediator for this relationship.Study Design A multisite prospective study was conducted in a sociodemographically diverse cohort of 647 pregnant women. At a study visit between 12 and 206/7 weeks' gestation, maternal psychosocial stress was assessed with six validated assessments and inflammation was measured via log-transformed serum concentrations of interferon-γ, interleukin (IL)-10, IL-13, IL-6, IL-8, and tumor necrosis factor-α. A composite stress score was calculated for each participant from the six stress assessments. The diagnosis of HDP was abstracted from the medical record and was defined as the presence of gestational hypertension after 20 weeks of pregnancy and/or preeclampsia. The association between composite stress and HDP was determined using binary logistic regression. Inflammation, using the six inflammatory biomarkers, was tested as a potential mediator between stress and HDP.Results Participants with higher composite stress scores were more likely to develop HDP (odds ratio [OR]: 1.50, 95% confidence interval [CI]: 1.06–2.12). When adjusted for known risk modifiers, including maternal age, race/ethnicity, parity, pre-pregnancy body mass index, diabetes, chronic hypertension, and smoking during pregnancy, the risk remained unchanged (OR: 1.50, 95% CI: 1.03–2.20). No mediation effect by inflammation was observed.Conclusion Independent of known risk factors, women exposed to greater composite stress burden across the life course are at increased risk of developing HDP.Key Points
Keywords: hypertensive disorders of pregnancy; preeclampsia; gestational hypertension; inflammation; psychosocial stress